Odpowiedzi

2010-02-15T18:27:43+01:00
2x+9y=-9
-3x+3y=8 /*(-3)

2x+9y=-9
-3-9y=-8
-x=-17 /:(-x)
x=17

2*17+9y=-9
34+9y=-9
9y=-9-34
9y=-43 /:9
y= - $ i siedem dziewiątych ..

Tak mi wyszło .. w tym (f).. !
2010-02-15T18:35:56+01:00
F) 2x + 9y = -9
-3x + 3y = 8 / *(-3)

2x + 9y = -9
9x-9y= -24
+-------------
11x=-33 / :11
x=-3

2x + 9y = -9
x=-3

9y=-9+6
x=-3

9y=-3 /:9
x=-3

y=-0,33
x=-3

g) 2x + 3y = 4 /*5
8x - 5y = -1 /*3

10x+15y=20
24x-15y=-3
+---------------
34x=17 / :34

x=0,5

x=0,5
2x + 3y = 4

x=0,5
3y=4-1=3 /:3

x=0,5
y=1